On origin of room temperature ferromagnetism in wide gap semiconductors - Korbecka, Anna; Majewski, Jacek A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
The emerging field of semiconductor spintronics would be dramatically boosted if a semiconductor exhibitingroom-temperature ferromagnetism could be found. Here, we discuss the recent stage of the research, paying particular attention to the understanding of observed room temperature ferromagnetism in wide band semiconductors, GaMnN and ZnMnO. Since the spinodal decomposition has been observed in these structures, we consider the possibilities to influence density fluctuations of the alloys to obtain ferromagnetic semiconductors with required functionalities. We contrast these compounds with (In,Mn)As and(Ga,Mn)As, where the ferromagnetism is well understood, albeit well below room temperature.